Aswaja and Al-Ma’un Theology in Brantas River Preservation: Local Muslim Environmental Activism and Indonesia’s Green Constitution - Fannani, Bakhruddin; Rohmah, Siti; Ma'arif, A. Samsul; Nur Arifuddin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2025)
The severe degradation of the Brantas River Basin calls for a reorientation of the Aswaja theology of Nahdlatul Ulama and the Al-Ma’un theology of Muhammadiyah, shifting from a theo-anthropocentric social movement to a theo-ecocentric ecological movement. Despite the growing scholarship on Islamic environmentalism, little attention has been paid to local Muslim activism in Indonesia, articulating ecological theology while engaging the Green Constitution as a national legal framework. This article analyzes the theological constructions of Nahdliyyin Front for Natural Resources Sovereignty (Front Nahdliyin untuk Kedaulatan Sumber Daya Alam/FNKSDA) and the Muhammadiyah Green Cadres (Kader Hijau Muhammadiyah/KHM) activists in the context of preserving the Brantas River Basin. Employing a qualitative phenomenological approach, the study interprets lived experiences captured through in-depth interviews, observations, and documentation. The findings demonstrate that both FNKSDA and KHM support the Green Constitution through the ecological reinterpretation of Aswaja theology and Al-Ma’un theology. FNKSDA emphasizes that the local Muslim communities are responsible for protecting the environment by refraining from dumping household waste and actively opposing polluting industries. KHM considers that the areas of ecological wasteland require protection and support from the community, corporations, and the government. This study highlights how local theological-activist models can inform global Muslim communities in integrating religious doctrines into environmental policy.